Pattern of ophthalmic consult from the ear, nose and throat ward of a tertiary hospital (2009)
Objective: To study the pattern and indications for ophthalmic referral of patients with otorhinolaryngology problems. Method: A retrospective study of patients who were admitted into the Ear, Nose and Throat (ENT) ward of the University College Hospital, lbadan and had ophthalmic referral between July 2000 and June 2004. The parameters evaluated were the demography of the patient, indication for ophthalmic consult, and the contribution of the ophthalmologist towards the management of the patient. Results: Reports on 26 patients on whom ophthalmic consults were sent were available for review. This accounted for 3% of the patients admitted during the period under review. Fourteen (53.8% ) of the consults were sent on account of proptosis and 7 (26.9%) for complaints of poor vision. In 12 (46.2%) of these patients, the otorhinotarfngological diagnosis was sinonasal tumour. The ophthalmologist made positive contributions to the management of 20 (76.9%) of the patients. These included the use of lubricants/protective shield (6 [23.1%]), tarsorrhaphy (3 [11.5%]), antiglaucoma medication (2{7.7%}) and cataract extraction (2[7.7%]). Conclusion: Proptosis milked highest for ophthalmic consult from the ENT ward in this review. Close collaboration between subspecialties should be encouraged when managing visllally-threatening conditions. There is also the need for a standard referral protocol.